Novel dietary herbal preparations with inhibitory activities against multiple SARS-CoV-2 targets: A multidisciplinary investigation into antiviral activities - Olujide Oludayo Olubiyi; Francis Alfred Attah; Birgit Strodel; Raphael Josef Eberle; Monika Aparecida Coronado; Oluwadotun Akinseinde; Augustine Anayochukwu Onyeaghala; Ikemefuna Chijioke Uzochukwu; Olayinka Adejoke Kotila; Hannah Dada-Adegbola; Awodayo Oluwatoyin Adepiti; Anthony Adebolu Elujoba; et al. (Food Chemistry Advances)
The outbreak of the COVID-19 pandemic has resulted in not <7.1million deaths globally as of December 2024. Many new variants of concern have continued to emerge since the initial outbreak of the original SARS-CoV-2 virus traceable to the Wuhan strain (Wuhan-Hu-1). In this work, the therapeutic potentials of four new polyherbal dietary preparations – VIVE (five plants), FORTE1(fortified VIVE), COMBI-5 (five spices) and MOK (Moringa seed) as well as four individual ethnomedicinal plants were investigated. Computational screening revealed chemical structures capable of establishing moderate to strong interaction with SARS-CoV-2′s main protease enzyme, while in vitro screening against the viral protease clearly established inhibitory potencies. The individual plant extracts making up VIVE and FORTE1 showed mild (494.9 ± 19.6 µg/ml) to moderate (21.5 ± 1.1 µg/ml) inhibitory activity against the viral enzyme in vitro; highest activity was obtained in the polyherbal VIVE preparation (17.3 ± 1.4 µg/ml). The MOK exerted total inhibition – 100 % (IC50 -3.6 ± 0.9) of the viral enzyme while COMBI-5 produced an inhibition of 95 %(IC50 - 0.9 ± 0.1). These results revealed the potential of specialized metabolites within these widely consumed dietary herbal products for the management of COVID-19 and related viral threats.